2014
DOI: 10.1103/physrevc.89.054320
|View full text |Cite
|
Sign up to set email alerts
|

Global performance of covariant energy density functionals: Ground state observables of even-even nuclei and the estimate of theoretical uncertainties

Abstract: Covariant density functional theory (CDFT) is a modern theoretical tool for the description of nuclear structure phenomena. The current investigation aims at the global assessment of the accuracy of the description of the ground state properties of even-even nuclei. We also estimate theoretical uncertainties defined here as the spreads of predictions within four covariant energy density functionals (CEDF) in known regions of the nuclear chart and their propagation towards the neutron drip line. Large-scale axi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
447
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(466 citation statements)
references
References 156 publications
(364 reference statements)
17
447
2
Order By: Relevance
“…The phenomenological fit of such functionals to bulk properties includes such effects in a somewhat averaged way, and as a consequence these functionals are relatively successful in the region of stable nuclei. Systematic investigations of relativistic density functionals [127,128] have shown that the various types of functionals produce rather similar results in the region of stable nuclei, where their parameters have been adjusted. There are, however, essential differences far from stability, and they are often caused by differences in the single-particle energies in those regions [129].…”
Section: Description Of Nucleus As a Relativistic Systemmentioning
confidence: 99%
“…The phenomenological fit of such functionals to bulk properties includes such effects in a somewhat averaged way, and as a consequence these functionals are relatively successful in the region of stable nuclei. Systematic investigations of relativistic density functionals [127,128] have shown that the various types of functionals produce rather similar results in the region of stable nuclei, where their parameters have been adjusted. There are, however, essential differences far from stability, and they are often caused by differences in the single-particle energies in those regions [129].…”
Section: Description Of Nucleus As a Relativistic Systemmentioning
confidence: 99%
“…Much of the nuclear landscape of bound nuclides remains unexplored [1,2]. The one-and two-proton drip lines lie relatively close to the line of beta stability due to the presence of the Coulomb barrier that has a confining effect on the proton density.…”
mentioning
confidence: 96%
“…The plenitude of available data has allowed for detailed investigations of the evolution of nuclear radii for isotope sequences along virtually the entire periodic table. These studies have revealed unexpected trends, especially close to magic numbers, which serve as benchmarks for nuclear structure calculations [3].…”
Section: Introductionmentioning
confidence: 99%